Exploring psychological distress experiences among intensive care unit nurses while caring for Covid-19 patients - Mohamed Ludin, Salizar; Ahmad Faisal, Nur Aqeela (2023)
The COVID-19 pandemic has caused significant psychological distress among ICU nurses caring for COVID-19 patients. Many of these nurses have been subjected to increased workload, social isolation, and heightened anxiety and fear due to the challenging circumstances they face. Developing coping strategies can improve nurses' psychological well-being, patient care, and healthcare system resilience during challenging times like a pandemic